To Flex or Rest: Does Adding No-Load Isometric Actions to the Inter-Set Rest Period in Resistance Training Enhance Muscular Adaptations? A Randomized-Controlled Trial - Schoenfeld, Brad J.; Grgic, Jozo; Contreras, Bret; Delcastillo, Kenneth; Alto, Andrew; Haun, Cody; De Souza, Eduardo O.; Vigotsky, Andrew D. (Frontiers in Physiology, 2020)
We aimed to investigate the effects of resistance training (RT) combined with no-load isometric actions (iso-holds) during the inter-set recovery period versus RT that involves passive inter-set rest on muscular strength, muscular hypertrophy, and muscular endurance in resistance-trained men. Twenty-seven resistance-trained male volunteers were randomly assigned to either a traditional group (TRAD) that performed a hypertrophy-oriented RT routine with the rest intervals spent passively (n = 13) or to a group that supplemented traditional RT with iso-holds (ISO) for the working muscle group between each set (n = 14). Training for both routines consisted of three weekly sessions performed for 8 weeks. Three sets of 8–12 repetitions were performed per exercise. A 2-min rest interval was afforded between sets; the ISO group performed iso-holds for the first 30 s of each rest interval and then recovered for the final 90 s. Maximal strength was assessed using the one repetition maximum (1RM) tests in the leg press and bench press. Upper-body muscle endurance was assessed by performing the bench press to failure at 50% of 1RM. Muscle thickness (MT) of the elbow flexors, elbow extensors, mid-thigh, and lateral thigh was assessed using B-mode ultrasound. Results indicated a favorable effect of ISO on MT in the mid-thigh. Alternatively, there was a possible detrimental effect for ISO on leg press strength. No other notable differences were seen between conditions. In conclusion, the use of inter-set iso-holds may be a time-efficient strategy to enhance development of the quadriceps femoris; conversely, it may be detrimental to maximizing lower body strength.